Ocorrência de neoplasias em cães atendidos no hospital veterinário da UFMT - Stocco, Matias Bassinello (2015)
Given the growing importance of the cases of oncology in veterinary clinic of small animals and the increasing owners’ care dedicated to their animals, neoplastic diseases have been recorded as having increased expression. This study aims to establish the occurrence of malignancies observed in dogs treated at the Veterinary Hospital of the Federal University of Mato Grosso (UFMT). 399 dogs were evaluated from April 2013 to April 2014, with a total of 470 histological and cytological examinations, obtaining a total of 524 results. Data such as race, gender, age and location of the tumors were obtained. The neoplasms were viewed with greater incidence in the abdomen (135; 34%), followed by genital region (106; 27%), head (41; 10%), general (33, 8%), chest (31; 8%) neck (23; 6%) forelimb (14; 3%), pelvic limb (12.3%) and perianal region (4; 1%). 524 results evaluated (300; 57%) had malignant tumors 150 (29%) and benign tumors and 74 (14%) had non-neoplastic changes. Among the malignant tumors, TVT (81; 27%) was the most prevalent tumor and from the benign, was the adenoma (31; 19%).